A Patient with Expanded Dengue Syndrom - Kirnia Tri Wulandari; Tikto Tikto (Green Publisher Indonesia, 2021)
EDS is an atypical manifestation of dengue infection that affects a variety of organ systems including gastrointestinal, hepatic, neurological, cardiac, pulmonary, and renal. It is one of the leading causes of hospitalization and death in children. A number of hypotheses have been proposed, but multifactorial pathogenesis. Severe cases can be expressed with petechiae, epistaxis, gastrointestinal hemorrhage, ascites, pleural effuse, heart attack, hypotension, tachycardia, changes in consciousness, fulminant hepatitis, and myocarditis. EDS-shaped organ dysfunction may require multidisciplinary management support for aggressive and effective action. The baby girl, An.P, 10 months old, came to the ER with a high fever since 4 days before KRS. High fever accompanied by vomiting and diarrhea. From a physical examination, the general condition of mentis compost, pulse, and breathing within normal limits. There are no epistaxis. The laboratory showed platelets of 100,000 μ/L, hematocrit 35.5%, hemoglobin (Hb) 12.3g/dL. Patients are diagnosed with dengue fever. in the same case that occurs in Mexico this is a case where patients with fever and headache. Patients exhibit neurological damage in which cranial Computerized Axial Tomography (CAT) reveals severe cerebral edema. Platelets 143,000 μ /L, Hb 10.6 g / dL, reported serologic NS1 positive. Patients die five days after hospital admission.Low incidence of EDS due to asymptomatic and easily missed diagnosis. This case has multi-organ failure. neurological manifestations such as seizures and decreased consciousness, gastrointestinal manifestations such as ascites and gastrointestinal bleeding, lung manifestations such as dyspnea. Conditions worsen in a fast time.